Improvement of hydrogen detection sensitivity of palladium film by in-plane compressive plastic deformation and application to hydrogen gas sensor. (1st December 2022) - Kato, Fumihito; Ato, Hiroki; Ichikawa, Shoichi; Kimura, Masahito; Hasegawa, Taiki; Ryunosuke, Ryuzaki; Masumoto, Noriyasu; Suzuki, Manabu; Ogi, Hirotsugu
Abstract: The hydrogen energy, which is environmentally friendly and does not emit carbon dioxide, has been attracting attention as an alternative fuel to the fossil fuel. In the shift to a hydrogen energy society, the highly sensitive hydrogen gas sensor has been required for the storage and management of hydrogen gas. In this study, we propose a film deposition method to induce the in-plane plastic deformation in the thin film and apply it to a hydrogen gas sensor, where the palladium film formed by this method is deposited on a thin quartz resonator. It is found that the sensor chip with the plastically deformed palladium film is about 1.5 times more sensitive than the conventional sensor chip and has high-speed response. The developed sensor is a novel device that can be used in an oxygen-free environment without any temperature compensation and constant heating.